MANAGEMENT IN EARLY CHILDHOOD EDUCATION: preschool principals, their knowledge and their training - Miglioranga Galisteu, Renata Boiatti; Nono, Maevi Anabel [UNESP] (Univ Fed Sao Paulo, Dept Education, 2021)
This article presents the results of a master's research that focused on the management of Early Childhood Education, more specifically in preschool, based on the investigation of school principals' knowledge about their profession. The specificity of the management in this stage of Basic Education and the importance of the directors of daycare centers and preschools in the establishment of a quality Early Childhood Education have been pointed out in recent studies, as well as research gaps in this area (KRAMER, 2011; FERNANDES; CAMPOS, 2015; CAMPOS et al., 2012). The study reported here, of a qualitative nature (ANDRE, 2013), aimed to identify, from the point of view of the subjects, the knowledge necessary for their performance in the management of preschools and the contributions and limitations of their initial and continuing training courses for acting as a school principal who serves children aged four to five years. Seven preschool principals from a municipality in the northwest of Sao Paulo were interviewed. Results point to the need for training policies for these professionals that focus on the specificity of management in the institutions that serve young children.
Keywords: Early Childhood Education; Preschool; Manager Training